2002
DOI: 10.2174/0929866023408931
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a new Lectin from the Red Marine Alga Hypnea Musciformis

Abstract: A lectin from the red marine alga Hypnea musciformis (HML) was purified by extraction with 20 mM PBS, precipitation with 70% saturated ammonium sulphate, ion-exchange DEAE-Cellulose chromatography and RP-HPLC. The 9.3 kDa polypeptide agglutinates erythrocytes from various sources and shows oligomerization tendencies under certain MALDI-TOF/MS conditions. Preliminary N-terminal sequencing and biological assays strongly suggest that the HML may belong to a new class of algae lectins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 0 publications
4
13
0
2
Order By: Relevance
“…Moreover, they do not appear to require metal ions, showing a high content of acidic residues and, even at high concentrations, tend to stay in the monomeric form (2)(3)(4). It has been shown (5) that aqueous extracts of the red marine algae Hypnea musciformis and H. cervicornis present hemagglutinating activity, and a recent study (6) reported the purification and characterization of a new lectin from H. musciformis that agglutinates erythrocytes from various sources.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they do not appear to require metal ions, showing a high content of acidic residues and, even at high concentrations, tend to stay in the monomeric form (2)(3)(4). It has been shown (5) that aqueous extracts of the red marine algae Hypnea musciformis and H. cervicornis present hemagglutinating activity, and a recent study (6) reported the purification and characterization of a new lectin from H. musciformis that agglutinates erythrocytes from various sources.…”
Section: Introductionmentioning
confidence: 99%
“…Lectins from marine algae Cystoclonium purpureum [74], Gracilaria verrucosa [75], Palmaria palmata [76], Solieria robusta [62], Gracilaria tikvahiae [60], Bryothamnion seaforthii and B.triquetrum [66], Solieria filiformis [77], Enantiocladia duperreyi [78], Amansia multifida [73], Hypnea musciformis [79], Gracilaria ornata [80], Hypnea cervicornis [81] and Georgiela confluens [82] were isolated by exchange chromatography, usually on DEAE cellulose. In contrast, due usually algal lectins have binding specificity of complex sugars, affinity chromatography has been used a few times, such as the lectins of green algae of the genus Codium [83,84,85], lectins from Ulva lactuca [86], Caulerpa cupressoides [87], Enteromorpha prolifera [88], Ulva pertusa [89], Bryopsis plumosa [90,91,92], Bryopsis hypnoides [93] and lectins from red marine algae of the genus Ptilota [68,69,70].…”
Section: Marine Algae Lectinsmentioning
confidence: 99%
“…H. musciformis has great economic value for the production of κ-carrageenan, an industrially important sulfated polysaccharide (Oliveira, 1998;Reis et al, 2006), and has shown antiviral activity against HSV (herpes simplex virus) and HIV (human immunodeficiency virus) (Neushul, 1990). H. musciformis also contains lectins, which have anti-inflammatory and hemagglutinating activity, besides being useful in cancer diagnosis (Nagano et al, 2002;Nagano et al, 2005). Extracts of H. musciformis also proved to have anthelmintic, anti-inflammatory, myo-relaxing and antifungal action (Salimabi, 1980;Davies et al, 1984;Melo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%